Aftermath : surviving the loss of God - Crosby, John F., 1955- (Algora Publishing, 2013)
Increasing numbers of disillusioned and thoughtful persons find they can no longer maintain a simplistic concept of theism, be it Christian, Jewish, or Islamic. But the shock that comes with loss of faith, and the challenges of learning to restructure one's life if one has been a believer, can seem overwhelming. ""Aftermath"" gives a sound foundation for building a meaningful life without god.